P-465 A systematic review and meta-analysis of ovarian stimulation outcomes in cancer patients opting for oocyte cryopreservation prior to treatment compared to social egg-freezers. (30th June 2022) - Lutaaya, N; Ní Dhonnabháin, B; Elfaki, N; Petrie, A; Hardiman, P.J; Saso, S; Getreu, N
Abstract: Study question: Do patients with malignancy undertaking oocyte cryopreservation (OC) prior to cancer treatment have comparable cycle outcomes to patients having OC for social reasons? Summary answer: Cancer patients achieve similar oocyte yields following ovarian stimulation to social freezers. However, they express lower peak oestradiol (E2), antral follicle count(AFC), and anti-Mullerian hormone(AMH). What is known already: Increasing numbers of women are diagnosed with cancer in their reproductive years. Medical advances have led to earlier detection, improved treatments, and higher survival rates. However, cytotoxic cancer therapy is known to have a negative impact on ovarian reserve and fertility. Oocyte cryopreservation prior to such treatments provides a means of preserving fertility. Statistics on cycle outcomes often comes from social egg-freezers, however it is not yet known if patients with malignancy opting to preserve oocytes prior to treatment can expect the same results as their healthy counterparts. Study design, size, duration: A literature search was performed on databases MEDLINE, EMBASE and Web of Science. Relevant text words and MeSH headings were used to identify all relevant papers. Studies reporting cycle outcomes of either oncology patients or social egg-freezers, or compared both were included. Only manuscripts that reported the number of mature oocytes obtained through controlled ovarian stimulation were included. Participants/materials, setting, methods: All patients presenting for oocyte cryopreservation prior to cancer therapy were included with no distinction made between cancer type. Controls included women presenting for oocyte cryopreservation for social reasons. Those presenting for male-factor infertility were not included. Data extracted included patient age total number of oocytes retrieved, peak E2, AFC, AMH, gonadotropin dose, and days of stimulation. Statistical heterogeneity was calculated and outcomes were presented to a 95% confidence interval (CI). Main results and the role of chance: A search of the databases retrieved 3805 articles, 116 of which remained for full-text evaluation after duplicates were removed and article titles and abstracts were assessed. Twenty-two articles met the inclusion criteria and were included in the meta-analyses. Total number of oocytes retrieved was similar between both groups with no significant difference in the means [standard mean difference mean difference (SMD) 1.069, 95% CI -1.1169 to 3.2549]. Peak E2, AFC, and AMH were all significantly lower in cancer patients with a SMD of -1031.4 (95% CI -1805.2 to -257.7), 0.277 (95% CI 0.042 to 0.511), and -2.289 (95% CI -3, 913 to -0.665) respectively. There was no significant difference observed in number of mature (M2) oocytes, total gonadotropin dose or number of stimulation days with an SMD of -0.022 (95% CI -1.861 to 1.817), 188.75 (95% CI- 432.86 to 810.35), and 0.002 (95% CI -0.439 to 0.443) respectively. Limitations, reasons for caution: Population characteristics, age, and BMI (major factors in fertility prognostics) were inconsistent between studies. Differences in cancer type, stage, grade, and stimulation protocols also potentially contributed to high heterogeneity. Few studies report obstetric outcomes, which could not be evaluated. Live-birth rate has arguably greater clinical significance but requires improved reporting. Wider implications of the findings: This research supports the view that cancer negatively impacts ovarian reserve and supports an argument for improved patient access to fertility preservation. As clinical practice improves cancer survivor rates, a responsibility lies with healthcare professionals to provide evidence-based and accurate counselling for patients to make informed decisions about their fertility. Trial registration number: Not applicable